ВИСОКОВОЛЬТНИЙ ПЕРЕТВОРЮВАЧ ДЛЯ ЕЛЕКТРОРОЗРЯДНОГО ЗНЕШКОДЖЕННЯ ДІОКСИДУ СІРКИ - Переверзєв, А.В.; Литвиненко, Т.М. (Інститут електродинаміки НАН України, Київ, 2015)
Adduced description and results of experimental research of high-voltage transducer. It is shown that the formation process of charge of the first capacitor storage energy with using IGBT devices leads to reduction of energy losses and increases the efficiency of the high-voltage converter. Done the comparison of experimental data with simulation results. Testing the experimental sample showed a significant efficiency of the developed high-voltage converter for neutralization of sulfur dioxide. The degree of neutralization reaches 96 %. References 12, figures 5.